Pricing Information Goods: A Strategic Analysis of the Selling and Pay-per-Use Mechanisms - Balasubramanian, Sridhar (Institutional Knowledge at Singapore Management University, 2015)
We analyze two pricing mechanisms for information goods. These mechanisms are selling, where up-front payment allows unrestricted use, and pay-per-use, where payments are tailored to use. We analytically model a market where consumers differ in use frequency and where use on a pay-per-use basis invokes a psychological cost associated with the well known "ticking meter" effect. We demonstrate that pay-per-use yields higher profits in a monopoly provided the associated psychological cost is low. In a duopoly, one firm uses selling and the other uses pay-per-use. Here, in contrast to the monopoly, selling yields higher profits than pay-per-use. We demonstrate that, surprisingly, the profits of both duopolists can increase as the psychological cost associated with pay-per-use increases. Next, we show that uncertainty in consumer use frequency does not affect pay-per-use in a monopoly, but lowers profits from selling. In a duopoly, both the seller and the pay-peruse provider obtain lower profits when use frequency is uncertain. We also analyze how pricing mechanism performance is affected if the firms cannot commit to prices, if the pay-per-use provider offers a two-part tariff, and if consumers are risk-averse.